Cuentos hispanofilipinos Hispano-Philippine stories - Farolan, Edmundo 1943-; Constancia, Paulina (Quezon City Central Book Supply, 2009)
Short novel on the lives of Don Francisco de Paula and his family.
Keywords: Short stories, Philippine (Spanish) -- Collections; Short stories, Philippine (Spanish) -- Translations into English; Philippine fiction (Spanish) -- Collections